2020
DOI: 10.1007/s10880-020-09724-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of Burnout with Emotional Coping Strategies, Friendship, and Institutional Support Among Internal Medicine Physicians

Abstract: Physician burnout influences physician mental health, staff stress, safety events, and patient outcomes. The association of burnout with compassion satisfaction, secondary stress, emotional coping strategies and many psychosocial variables, such as institutional support, friendship, and spirituality, have not been well studied. A convenience sample of internal medicine physicians was emailed a survey using validated instruments to explore these associations. The response rate was 337/1021 (33%), with a burnout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 28 publications
(32 reference statements)
4
30
0
6
Order By: Relevance
“…In terms of coping, higher use of dysfunctional coping strategies was associated with clinically significant psychological distress. This is consistent with previously reported association between avoidant coping strategies and burnout and lower compassion satisfaction in the medical setting (Doolittle, 2020 ). Moreover, avoidant coping was associated with the perceived stress during the pandemic in an Italian study (Babore et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…In terms of coping, higher use of dysfunctional coping strategies was associated with clinically significant psychological distress. This is consistent with previously reported association between avoidant coping strategies and burnout and lower compassion satisfaction in the medical setting (Doolittle, 2020 ). Moreover, avoidant coping was associated with the perceived stress during the pandemic in an Italian study (Babore et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…The study revealed an association between positive coping strategies (including acceptance, grit, reframing) and lower levels of burnout and superior compassion. Furthermore, friendship was associated with lower levels of burnout and higher levels of compassion satisfaction [6].…”
Section: Studies Measuring Wellness In Healthcare Providersmentioning
confidence: 95%
“…The questionnaire is available as an appendix in the original validation manuscript. 33 In addition to the three primary instruments, a subscale of the Professional Quality of Life Scale (ProQol) 34 has also been used to measure burnout in several studies. 35 The ProQol is a 30-item instrument with ten questions each addressing compassion satisfaction, secondary traumatic stress, and burnout.…”
Section: Burnout Measurement Instrumentsmentioning
confidence: 99%